The problem of Muslim national identity in Myanmar - Salaam, Myint Thein (a) Abdus (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2012)
This study examines the identity of Muslim communities in Myanmar (Burma) based on their ancient origins and settlements in Myanmar and their struggle to maintain their national identity under successive governments. The results of this study confirm that Muslim communities in Myanmar, namely Burman Muslims (including Pathi, Myedu and Zerbadee), Rakhine Muslims (including Rohingya and Kaman), Panthay Muslims (Chinese) and Pashu Muslims (Malay) have historically evolved and are stable communities, like other ethnic groups of Myanmar, and that they are by right Myanmar nationals. This study shows that Muslim communities at Burma's independence automatically had Burmese citizenship, the same status as all other citizens of Burma, and that they were among the 144 national races of Burma until 1982. However, they gradually lost their status, rights and privileges after the military coup led by General Ne Win, in 1962. It is the main finding of the present research that the 1982 Burma Citizenship Law created by General Ne Win did not only deliberately target the Rohingyas in Rakhine State to make them “Stateless” and refugees, but also degraded most of the Muslims and other minorities throughout the country to become second class or third class citizens without any justification. This study also found that the 1982 Burma Citizenship Law is contrary to the basic principles of the United Nations Charter, human rights and international norms.